Model Pengembangan Kurikulum Merdeka Berbasis Integrasi Indigenous Knowledge - Rozi, Muhammad Fathur (Civiliza Publishing, Indonesia., 2024)
This research aims to provide insight and inspiration for educators, curriculum developers and other stakeholders in enriching students' educational experiences through the integration of Indigenous Knowledge in the independent curriculum. An independent curriculum refers to an approach that places students as active subjects in the learning process. This research uses a qualitative approach with a case study method. The data collection techniques used were observation, interviews and documentation. Testing the validity of data in qualitative research uses triangulation, while data analysis uses data reduction, data display or data presentation, and conclusion. The research results of this research are; (1) adapting the curriculum to the vision of the institution, (2) developing learning materials and resources, (3) training and support for teachers with an independent curriculum development model based on the Integration of Indigenous Knowledge (indigenous knowledge) using the Beauchamp model with steps to respect cultural diversity, determining curriculum coverage, determining the parties involved, formulating the objectives, implementation and implementation of the curriculum and evaluation.